2015
DOI: 10.1007/s11244-015-0428-3
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Biomass-Derived 2-Hexanol to Liquid Transportation Fuels: Study of the Reaction Mechanism on Cu–Mg–Al Mixed Oxides

Abstract: The reaction mechanism of 2-hexanol conversion to high molecular weight compounds to be used as liquid transportation fuels was studied on MgO, Cu/SiO 2 and a bifunctional Cu-Mg-Al mixed oxide with 8 wt% Cu (catalyst 8.0CuMgAl). Catalysts were characterized by several physical and spectroscopic techniques. The evolution of 2-hexanol conversion and yields in inert (N 2 ) and reducing (H 2 ) reaction atmospheres at different contact times (W/F 0 ) was investigated, which allowed distinguishing between primary an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Cu and Ni are the metals most often used for this purpose owing to their activity in alcohol dehydrogenation.D iC osimo et al obtained am ixture of C9-C24 oxygenates and hydrocarbons with yields up to 91 %t hrough gas-phase upgrading of 2-hexanol at 300 8Co ver aC u-Mg-Al oxide containing 8% of Cu. [16] The authors compared these results with those obtained in the presence of aC u/SiO 2 catalyst with the same loading of Cu but in this case no CÀCb onds were formed, thus suggesting that Cu 0 particlesa re responsible only for the dehydrogenation-hydrogenation steps. In contrast, coupling reactions are promoted by Mg 2 + ÀO 2À couples but the authors found an optimal amount of Al, surroundingt hese couples and giving account of the very high selectivity observed.…”
Section: Guerbet Condensation Reactionsmentioning
confidence: 95%
See 3 more Smart Citations
“…Cu and Ni are the metals most often used for this purpose owing to their activity in alcohol dehydrogenation.D iC osimo et al obtained am ixture of C9-C24 oxygenates and hydrocarbons with yields up to 91 %t hrough gas-phase upgrading of 2-hexanol at 300 8Co ver aC u-Mg-Al oxide containing 8% of Cu. [16] The authors compared these results with those obtained in the presence of aC u/SiO 2 catalyst with the same loading of Cu but in this case no CÀCb onds were formed, thus suggesting that Cu 0 particlesa re responsible only for the dehydrogenation-hydrogenation steps. In contrast, coupling reactions are promoted by Mg 2 + ÀO 2À couples but the authors found an optimal amount of Al, surroundingt hese couples and giving account of the very high selectivity observed.…”
Section: Guerbet Condensation Reactionsmentioning
confidence: 95%
“…Di Cosimo et al. obtained a mixture of C9–C24 oxygenates and hydrocarbons with yields up to 91 % through gas‐phase upgrading of 2‐hexanol at 300 °C over a Cu‐Mg‐Al oxide containing 8 % of Cu . The authors compared these results with those obtained in the presence of a Cu/SiO 2 catalyst with the same loading of Cu but in this case no C−C bonds were formed, thus suggesting that Cu 0 particles are responsible only for the dehydrogenation–hydrogenation steps.…”
Section: Guerbet Condensation Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of aluminum and magnesium mixed oxides derived from hydrotalcites as support for impregnation of copper species and forward application in the dehydrogenation of alcohols is motivating. Aer heat treatment, these mixed oxides have various unique properties as providing an ideal balance of acid and base sites [13][14][15][16][17] and unique textural properties, which have impact on metals dispersion and therefore on ethanol conversion to acetaldehyde and ethyl acetate. 3,5 In a previous study, [18][19][20] an emulsion-mediated method was used to produce Al-Mg mixed oxides from hierarchically ordered hydrotalcite precursors that gave a high specic surface area.…”
Section: Introductionmentioning
confidence: 99%